2007
DOI: 10.1016/j.cell.2006.12.042
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Cooperative Folding of Small Naturally Occurring Proteins Is Likely the Result of Natural Selection

Abstract: To illuminate the evolutionary pressure acting on the folding free energy landscapes of naturally occurring proteins, we have systematically characterized the folding free energy landscape of Top7, a computationally designed protein lacking an evolutionary history. Stopped-flow kinetics, circular dichroism, and NMR experiments reveal that there are at least three distinct phases in the folding of Top7, that a nonnative conformation is stable at equilibrium, and that multiple fragments of Top7 are stable in iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
170
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(190 citation statements)
references
References 65 publications
(84 reference statements)
20
170
0
Order By: Relevance
“…It shows that the tendency to misfold does not necessarily diminish with increasing native stability: despite the high native stability of Top7, its folding kinetics is complex, probably involving multiple kinetic traps [154,155]. Theoretical considerations indicate that the lack of two-state-like behaviour of Top7 is probably caused more fundamentally by its peculiar native structure, more so than the fact that it is an artificially designed protein that did not undergo natural selection [156].…”
Section: Reconciling Evolutionary Selection For Stability With Marginmentioning
confidence: 99%
“…It shows that the tendency to misfold does not necessarily diminish with increasing native stability: despite the high native stability of Top7, its folding kinetics is complex, probably involving multiple kinetic traps [154,155]. Theoretical considerations indicate that the lack of two-state-like behaviour of Top7 is probably caused more fundamentally by its peculiar native structure, more so than the fact that it is an artificially designed protein that did not undergo natural selection [156].…”
Section: Reconciling Evolutionary Selection For Stability With Marginmentioning
confidence: 99%
“…Caching it inside a helix likely promotes metastable nonnative β-contacts between the two terminal hairpins, slowing down the folding. This may be one of the reasons for the slow and multiphase folding of Top7 observed in recent experiments (5). Our hypothesis could be tested through mutation experiments focusing on residues in Top7 that correspond to the N terminus of the CFr sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal hairpin is formed next (3), often away from the helix, before rearranging in a native-like position relative to the helix (4). The helix partially unfolds (5), and the released residues join with the hairpin to complete the native structure (6). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, it was suggested that the cooperativity of the folding reaction is the result of natural selection 39 . It is intriguing that AK e uses cooperative unfolding/refolding to accommodate a large-scale conformational change during catalysis.…”
mentioning
confidence: 99%